Preliminaries on the State-of-the-Practice on Smart Cities Projects in Brazil - Barros, David Antônio Teixeira de Moraes; Morais, Edison Andrade Martins; Kassab, Mohamad; Graciano Neto, Valdemar Vicente (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais Estendidos do XX Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi_estendido.2024.238855, 2024)
Smart cities emerge as a response to build the city of the future, where the well-being and rights of citizens are ensured under a sustainable perspective. Understanding the current state of smart cities in Brazil becomes essential to assess how technology is impacting urban dynamics in the country. In that sense, the main contribution of this paper is to present preliminary results of a systematic survey on smart city projects in Brazil. 21 professionals from 7 states and different areas responded to the survey. Results reveal that (i) there is a range of smart cities projects in different regions of Brazil; (ii) several technologies are already deployed in Brazilian cities, but (iii) infrastructure is one of the main challenges to make smart cities a full reality.